A simple method for estimating the roundness of minimum zone circle. Issue 1 (27th January 2020) - Huang, Q.; Mei, J.; Yue, L.; Cheng, R.; Zhang, L.; Fang, C.; Li, R.; Chen, L.
Abstract: With the rapid development of micromachining technology, the feature size of object parts becomes smaller whilst the required tolerance accuracy becomes higher. The geometry of these micro‐parts must be critically verified at sub‐micrometer or even nanometer accuracy in three dimensions to guarantee machining quality, such as the cylindrical parts. Therefore, the method for estimating roundness error plays an increasingly important role in machining. This paper focuses on the roundness estimation based on the minimum zone circle method in a Cartesian coordinate system. An asymptotic search method is also proposed to obtain the coordinates of the concentric centre of the minimum zone circle model and to calculate the roundness error. Comparison and simulation experiments are also conducted to test the performance of the proposed method. The results demonstrate that the proposed method is effective, reliable and can meet the requirements for roundness estimation. Abstract : In order to quickly and accurately estimate the roundness of minimum zone circle (MZC), an asymptotic search method is proposed to obtain the minimum zone circle centre through the process of global search, local search and fine search. After the global and local search, the quasi‐minimum zone circle centre, which is very close to the minimum zone circle centre, is determined. Then the quasi‐minimum zone circle centre is used to determine the minimum zone circle centre by establishing the mathematical models.